Simplification
- [5 - [3/4 + {21/2 - (1/2 + 1/6 - 1/7)}]] / 2 = ?
-
View Hint View Answer Discuss in Forum
? = [5 -[3/4 + {21/2 - (1/2 + 1/6 - 1/7)}]]/2
= [5 - [3/4 + {5/2 -(1/2 + 7 - 6/42)}]]/2
= [5 - [3/4 + {5/2 - (1/2 + 1/42)}]]/2
= [5 - [3/4 + {5/2 - (21 + 1 /42)}]]/2Correct Option: A
? = [5 -[3/4 + {21/2 - (1/2 + 1/6 - 1/7)}]]/2
= [5 - [3/4 + {5/2 -(1/2 + 7 - 6/42)}]]/2
= [5 - [3/4 + {5/2 - (1/2 + 1/42)}]]/2
= [5 - [3/4 + {5/2 - (21 + 1 /42)}]]/2
= [5 - [3/4 + {5/2 - 22/42}]]/2
= [5 - [3/4 + {105 - 22/42}]]/2
= [5 - [3/4 + 83/42]] / 2
= [5 - [63 + 166/84]]/2
= (191/84)/2
=191/168 = 123/168
- [0.5 x 0.5 x 0.5 + 0.2 x 0.2 x 0.2 + 0.3 x 0.3 x 0.3 - 3 x 0.5 x 0.3 x 0.2 ] / [0.5 x 0.5 + 0.2 x 0.2 + 0.3 x 0.3 - 0.5 x 0.2 - 0.2 x 0.3- 0.5 x 0.3] = ?
-
View Hint View Answer Discuss in Forum
Given expression
[a3 + b3 + c3 - 3abc] / [a2 + b2 + c2 - ab - bc - ca]
= a + b + cCorrect Option: A
Given expression
[a3 + b3 + c3 - 3abc] / [a2 + b2 + c2 - ab - bc - ca]
= a + b + c
= 0.5 + 0.2 + 0.3
where, a = 0.5, b = 0.2, c = 0.3
- If √2 = 1.4142, then the value of 7 / (4 + √2) is ?
-
View Hint View Answer Discuss in Forum
√7 / (4 + √2) = [7 / (4 + √2)] x [(4 - √2 ) / (4 - √2]
= 7(4 - √2) / (16 - 2)
[∵ (a + b)(a - b) = a2 - b2]
= 7(4 - √2 )/14Correct Option: C
√7 / (4 + √2) = [7 / (4 + √2)] x [(4 - √2 ) / (4 - √2]
= 7(4 - √2) / (16 - 2)
[∵ (a + b)(a - b) = a2 - b2]
= 7(4 - √2 )/14
= (4 - √2)/2
= (4 - 1.4142)/2
= 2.5858/2 = 1.2929
- The value of (0.96)3 - (0.1)3/ [(0.96)2 + (0.096) + 0.01] is ?
-
View Hint View Answer Discuss in Forum
(0.96)3 - (0.1)3/ [(0.96)3 + 0.096 + 0.01]
= (0.96)3 - (0.1)3 = (0.96 - 0.1) [(0.96)2 + 0.96 x 0.1 + (0.1)2]
[∵ a3 - b3 = (a - b) (a2 + ab + b2)]Correct Option: A
(0.96)3 - (0.1)3/ [(0.96)3 + 0.096 + 0.01]
= (0.96)3 - (0.1)3 = (0.96 - 0.1) [(0.96)2 + 0.96 x 0.1 + (0.1)2]
[∵ a3 - b3 = (a - b) (a2 + ab + b2)]
= (0.96 - 0.1) [(0.96)2 + 0.096 + 0.01]/(0.96)2 + 0.096 + 0.01
= 0.96 - 0.1 = 0.86
- If a + b + c = 14 and a2 + b2 + c2 = 96, then (ab + bc + ca) = ?
-
View Hint View Answer Discuss in Forum
Use this formula
(a + b + c)2 = (a2 + b2 + c2) + 2(ab + bc + ca)Correct Option: C
We know that,
(a + b + c)2 = (a2 + b2 + c2) + 2(ab + bc + ca)
⇒ 196 = 96 + 2(ab + bc + ca)
⇒ 2(ab + bc + ca) = 196 - 96 = 100
∴ (ab + bc + ca) = 100/2 = 50